Phytoplankton phosphorus limitation in a North Atlantic coastal ecosystem not predicted by nutrient load - Trommer, Gabriele; Leynaert, Aude; Klein, Cécile; Naegelen, Aurore; Beker, Beatriz (Journal of Plankton Research, 2013)
International audience